Multivariable transducer interfacing circuit for wireless monitoring of smart implants - Khan, Sheroz; Alam, A. H. M. Zahirul; Zainudin, Zuraidah; Khan, Muzna S.; Hameed, Shihab A.; Hassan Abdalla Hashim, Aisha; Islam, Md. Rafiqul (2009)
The increasing use of microprocessors and microcontrollers in measurement and data acquisition systems has necessitated the need for obtaining sensor response in a digital format, thus avoiding the need for an analog-to-digital conversion stage. Further, in quite of a number of automation applications, there is the need of wireless transmission of data signals over narrow gaps. The signal obtained is loaded with data from transducers measuring parameters of interest for monitoring or other reasons. Changes in resistive sensors as a result of parameters changes are obtained as a digital signal with its time-period, amplitude and duty cycle directly proportional to variations in three different resistors. This is one useful way of reading data signals from more than a single sensors at the same time by using a measurement circuit with a single output signal. The utility of this work lies in applications where the allowable room for proper wiring is either impossible or the congestion of wiring is be avoided for more clarity and better automation. The experimental results obtained in this paper match with the simulation details of the interface circuit.